2021
DOI: 10.1126/scitranslmed.abb5280
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity promotes infection by impairment of the innate antimicrobial defense function of dermal adipocyte progenitors

Abstract: Infections are a major complication of obesity, but the mechanisms responsible for impaired defense against microbes are not well understood. Here, we found that adipocyte progenitors were lost from the dermis during diet-induced obesity (DIO) in humans and mice. The loss of adipogenic fibroblasts from mice resulted in less antimicrobial peptide production and greatly increased susceptibility to Staphylococcus aureus infection. The decrease in adipocyte progenitors in DIO mice was explained by expression of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…By analyzing age-related changes in dermal fat in human skin, we have found that back skin is enriched with dWAT in neonates and that human dWAT becomes gradually lost during postnatal development and aging ( Zhang et al., 2019 ), indicating that adipogenic dFBs are also lost in human skin during aging. We also have found that whereas adipocytes are normally found in the lower dermis of lean subjects, adipocytes infiltrate through the upper dermis in the back skin of subjects who are obese ( Zhang et al., 2021a ). Another study shows that overfeeding in adult humans leads to adipocyte hyperplasia in the lower body subcutaneous adipose but not in the abdominal subcutaneous adipose ( Tchoukalova et al., 2010 ), suggesting that there is a regional difference in cellular mechanisms of AT growth in obesity.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…By analyzing age-related changes in dermal fat in human skin, we have found that back skin is enriched with dWAT in neonates and that human dWAT becomes gradually lost during postnatal development and aging ( Zhang et al., 2019 ), indicating that adipogenic dFBs are also lost in human skin during aging. We also have found that whereas adipocytes are normally found in the lower dermis of lean subjects, adipocytes infiltrate through the upper dermis in the back skin of subjects who are obese ( Zhang et al., 2021a ). Another study shows that overfeeding in adult humans leads to adipocyte hyperplasia in the lower body subcutaneous adipose but not in the abdominal subcutaneous adipose ( Tchoukalova et al., 2010 ), suggesting that there is a regional difference in cellular mechanisms of AT growth in obesity.…”
Section: Introductionmentioning
confidence: 66%
“…The proliferative and adipogenic potentials of preadipocytes were also negatively correlated with both BMI and adipocyte cell size of the donors ( Liu et al., 2017 ; Zhang et al., 2021a ). Work from our group or other groups has shown that TNF-α, TGFβ, and/or WNT secreted from enlarging mature adipocytes and/or infiltrated macrophages inhibit the adipogenic potential of preadipocytes and induce a proinflammatory and profibrotic phenotype in these cells, leading to impairment of adipocyte hyperplasia, amplification of tissue inflammation, and fibrosis during the chronic state of obesity ( Isakson et al., 2009 ; Liu et al., 2017 ; Zhang et al., 2021a ). Together, dysregulation of the release of adipokines and/or cytokines driven by adipocyte hypertrophy is a critical event that leads to adipose dysfunction and inflammation in obesity.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The γ isoform exists in all tissues, is predominantly expressed in adipose tissue, and is essential for the differentiation and function of adipocytes [ 27 , 28 ]. A previous study reported that PPARγ was the most highly expressed and necessary in adipocytes for differentiation and is regarded as a master regulator of adipogenesis and a key regulator of gene expression in matured adipocytes [ 29 , 30 , 31 ]. Besides these, recently, lots of experiments related to obesity in whole-body PPARα − deficient mice (PPARα −/− ) and in mice lacking PPARα only in hepatocytes (PPARα hep−/− ) were performed.…”
Section: Discussionmentioning
confidence: 99%